Implementation of PROMETHEE Method in Decision Support System for Student Competency Competition Participant Selection - Muhamad Rezka Al Anshori; Hadi Zakaria (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
The Student Competency Competition (Lomba Kompetensi Siswa/LKS) is a prestigious national-level event requiring vocational schools to select participants in an objective and measurable manner. However, the selection process at SMKN 1 Tangerang Selatan still relies on subjective teacher judgment and lacks comprehensive evaluation criteria, risking suboptimal decisions that may result in selected students being insufficiently competent for the competition. This research aims to design and implement a web-based Decision Support System (DSS) using the PROMETHEE (Preference Ranking Organization Method for Enrichment Evaluation) method to support objective, structured, and transparent LKS participant selection. Three evaluation criteria were defined based on field interviews: Practicum Subject (K1), Logic Subject (K2), and Attendance (K3), each processed through pairwise preference comparisons using linear and usual preference functions with equal criterion weights. The system was developed using JavaScript (Node.js) and MongoDB, supporting four user roles with distinct access rights. System correctness was verified through Black Box Testing across 16 functional scenarios and White Box Testing of four algorithmic modules using Cyclomatic Complexity analysis, all of which passed successfully. The ranking results identified A3 as the top-recommended candidate with the highest Net Flow value of +0.2083, demonstrating the system's ability to surface competency dimensions overlooked by manual evaluation. Based on a questionnaire involving 20 respondents, the system achieved a user satisfaction score of 87.6%, categorized as very strong. These findings confirm that the PROMETHEE-based DSS is a reliable, practical, and deployment-ready tool for supporting participant selection in vocational school environments. The findings of this study offer a replicable methodological framework for vocational institutions seeking to standardize competition-based participant selection through multi-criteria decision support.